2013
DOI: 10.2174/0929866511320060011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of the Ability of Online Available Prediction Programs to Predict True Linear B-cell Epitopes

Abstract: This work deals with the use of predictors to identify useful B-cell linear epitopes to develop immunoassays. Experimental techniques to meet this goal are quite expensive and time consuming. Therefore, we tested 5 free, online prediction methods (AAPPred, ABCpred, BcePred, BepiPred and Antigenic) widely used for predicting linear epitopes, using the primary structure of the protein as the only input. We chose a set of 65 experimentally well documented epitopes obtained by the most reliable experimental techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Previously, Costa et al [] showed that ABCpred to give the best results compared to BepiPred and other online prediction methods used for predicting linear epitopes. The experience in our study was similar and showed a best epitope pair with one amino acid change that is conserved in all 12 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Costa et al [] showed that ABCpred to give the best results compared to BepiPred and other online prediction methods used for predicting linear epitopes. The experience in our study was similar and showed a best epitope pair with one amino acid change that is conserved in all 12 genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The ABCpred algorithm was shown to have a better predictive performance, as compared with various physicochemical properties, including hydrophilicity ( 15 ), flexibility ( 27 ) and accessibility ( 28 ). In addition, Costa et al ( 29 ) demonstrated that AAPPred and ABCpred obtained the best results in terms of epitope prediction, as compared with other programs, although AAPPred is no longer available. BepiPred is a traditional algorithm developed by Larsen et al ( 14 ) in 2006 using 14 epitope-annotated proteins and a human immunodeficiency virus dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Methods that have been used for the identification of B cell (including IgE) epitopes include enzymatic cleavage, peptide arrays, phage display techniques, peptide microarray-based immunoassay, Nuclear magnetic resonance spectroscopy and X-crystallography [7]. However, these methods are considered expensive and time consuming [8].…”
Section: Introductionmentioning
confidence: 99%